Discovering Decision Rules in the Commodity Options Market for Hedging Against Oil Price Fluctuations - Lamasz, Bartosz; Puka, Radosław; Skalna, Iwona (International Journal of Energy Economics and Policy, 2025)
High volatility of commodity prices is due, among others, to sudden global events. Only recently, COVID-19 pandemic and the war in Ukraine have caused crisis in commodity markets. In particular, the prices of strategic goods such as oil have become very volatile. To hedge against adverse price movements in this commodity, business and investors use commodity options. However, making reasonable buy/sell decisions requires a good mix of market understanding, technical and fundamental analysis, and risk management. In this paper, we use association analysis to discover buy decision rules for the investors in the WTI crude oil options market. The rules are discovered based on moving averages of WTI crude oil prices and the price differences of this commodity between selected days. The effectiveness of the discovered rules is evaluated using indicators related to the level of payout of the buyer of call options and the cost of acquiring these options. The results of experiments on data from 26 August 2008 and 15 November 2022 indicate that the decision rules discovered can effectively support decisions to take a long position in call options and can significantly contribute to effective hedging against unfavorable oil price movements.